INPUTS USE OPTIMIZATION OF A CROP-LIVESTOCK-FOREST INTEGRATION SYSTEM WITH PRECISION AGRICULTURE TOOLS - Bernardi, A. C. de C.; Laurenti, N.; Bettiol, G. M.; de Oliveira, P. P. A.; Alves, T. C.; Pedroso, A. de F.; Esteves, S. N.; Pezzopane, . R. M. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Knowledge on spatial variability of soil properties is useful for the rational use of inputs, as in the site-specific application of lime and fertilizer in the crop-livestock-forest integrated systems (CLFIS). Precision agriculture (PA) is the tool to improve the efficiency of use of these issues. The objective of this research was to evaluate liming and fertilizer variable rate application in CLFIS. The field study was carried out in a 30-ha area at Embrapa Pecuária Sudeste in São Carlos, SP, Brazil. Soil samples were collected at 0-0.2 m depth, and each sample represented a paddock. The spatial variability of soil properties and site-specific liming and fertilizer need were modeled by inverse distance weighting (IDW) technique. The results showed that spatial analysis of liming and fertilization needs can provide management tools for pasture management. And variable rate lime and phosphate fertilizer application technology can be used as a soil correction and fertilization tool leading to greater homogeneity of soil chemical attributes.